(untitled) - Daepp , Ulrich; Gorkin, Pamela (Springer, 2011)
Springernature.com; Undergraduate Texts in Mathematics
Keywords: Toán học -- Đọc -- Viết -- Chứng minh mệnh đề; Mathematics -- Reading -- Writing -- Proving